A comparative analysis of the policy process of elite sport development in China and the UK (in relation to three Olympic sports of artistic gymnastics, swimming and cycling) - Zheng, J. (2015)
This thesis seeks to analyse the policy making and policy implementation processes of elite sport in China and the UK, covering the period 1992-2012. Three sports are selected for detailed cases studies: artistic gymnastics, swimming and cycling. They represent a wide range of sports in two countries, based on their varying competiveness, weights and traditions. Key areas including organisational structure, financial support, talent identification and athlete development, coaching, training, competition opportunities, scientific research and others (including international influence and other sport- and country-specific areas) are identified to organise the discussion. The aim is not only to present key characteristics of the development of each sport in China and the UK respectively and to introduce the successful experience and problems but also to form a basis for the discussion of policy making, policy implementation and policy changes. Hence, a series of policy making and implementation theories and frameworks are utilised. The focus is on meso-level policy frameworks. However, the thesis cannot embrace all frameworks and the focus is narrowed to the multiple streams framework and the policy community framework. These two frameworks' roles are not confined to helping organise the discussion of policy processes in the three sports in the two countries. More importantly, their quality and applicability will be evaluated. Furthermore, globalisation theory, theories of policy learning and transfer, policy implementation and policy instruments are also included to provide a more holistic analysis of the policy processes. Generally speaking, all these policy making and implementation theories provide valuable lenses to understand policy processes in the three sports in China and the UK and equally importantly help explain policy changes. When it comes to the applicability, both the multiple streams framework and the policy community framework are largely applicable to China. However, the former's applicability to China is confined to its structural factors while the fundamental assumptions of organisational anarchy and the ambiguity of policy making and its pluralistic basis seem to have limited compatibility with China. Moreover, some changes and adaptations need to be made in terms of the structural factors. For example, the 18 concept of policy windows can be further specified in elite sport in China while the usefulness of the concept of policy entrepreneurs is limited due to the difficulty of identifying groups of policy entrepreneurs outside the government bureau. In comparison, the policy community framework and the concept of policy monopoly sit comfortably with the case of China where key elements of policy community and policy monopoly are very strong and typical. Last, this thesis demonstrates the value of integrating different policy theories, most notably the integration of the multiple streams framework and the policy community framework in the analysis of elite sport in China.